BALANCING SUSTAINABLE TOURISM DEVELOPMENT WITH LOCAL REGULATION: A CASE STUDY OF SURANADI VILLAGE'S EFFORTS IN ENVIRONMENTAL CONSERVATION AND CULTURAL PRESERVATION - I Wayan Bratayasa (Bajang Institute, 2023)
This research delves into the intricate dynamics surrounding the Suranadi Village Local Regulation of 2022, a pivotal milestone in the village's journey towards sustainable tourism development. By examining the multifaceted impacts and challenges arising from the implementation of this regulation, our study unveils a compelling narrative of environmental conservation, cultural preservation, and community engagement. We uncover the regulation's remarkable successes in mitigating environmental degradation, preserving the village's cultural heritage, and empowering its local community. However, we also illuminate the delicate balance between conservation and economic growth, as some local businesses face profitability challenges due to stringent regulations. Our findings underscore the importance of adaptive governance, continuous stakeholder consultation, and harmonious integration of conservation and economic prosperity in sustainable tourism efforts. Suranadi Village emerges as a beacon of hope in the global tourism landscape, offering valuable insights for destinations striving to harmonize responsible tourism with environmental stewardship, cultural authenticity, and community well-being